Lipidomic profile of seminal plasma in non-obstructive azoospermia with sperm maturation arrest - S. I. Gamidov; T. V. Shatylko; A. Kh. Tambiev; A. O. Tokareva; V. V. Chagovets; T. B. Bitsoev; N. L. Starodubtseva; A. Yu. Popova; V. E. Frankevich (Вестник урологии)
Introduction. The difference between obstructive and non-obstructive azoospermia with sperm maturation arrest is important for the choice of treatment tactics and adequate counseling of a married couple.Purpose of the study. The study aimed to assess the semen lipid profile in patients with sperm maturation arrest. Materials and methods. Samples of seminal plasma for lipid composition of 24 men with normozoospermia and 64 men with azoospermia were studied. Patients with azoospermia underwent microdissection testicular biopsy followed by the detection of testicular tissue pathology. Lipid extracts were analyzed by liquid chromatography with mass spectrometry. Lipid data were compared with the results of pathomorphological studies.Results. Comparison of two groups revealed a statistically significant concentration differences for 22 lipids detected in positive-ion mode and 11 lipids detected in negative-ion mode. Those lipids mainly belong to the classes hexosylceramides, sphingomyelins and phosphatidylcholines — simple ethers and oxidized lipids. In multivariate analysis, the following lipids were found to be statistically significant predictors of sperm maturation arrest: PC 16: 0_22: 6 lipid (β-coefficient: -0.73; 95% confidence interval (95% CI): -1.42 to -0.27; odds ratio (OR): 0.48; OR CI: 0.24 to 0.76; Wald's test: -2.58; p = 0.01), SM d20: 1/22:2 lipid (β-coefficient 4.96; 95% CI 2.29 to 9.13; OR: 142.31; OR CI: 9.90 to 9.22^103; Wald's test: 2.93; p = 0.003); PG 20:3_22: 6 lipid (β-coefficient 2.52; 95% CI 1.13 to 4.49; OR: 12.37; OR CI: 3.10 to 89.27; Wald's test: 3.02; p = 0.002); PC O- 16: 1/16:0 lipid (β-coefficient 1.96; 95% CI -4.12 to 0.27; OR: 0.14; OR CI: 0.02 to 0.76; Wald's test: -2.05; p = 0.04). The prediction model characteristics of sperm maturation arrest, obtained during cross-validation in the positiveion mode composed: sensitivity 91%, specificity 85%; in negative-ion mode: sensitivity 75%; specificity 81%.Conclusions. Even though early stages of spermatogenesis are equally preserved in both fertile men and men with homogeneous sperm maturation arrest, the semen in the studied group of patients differed in its lipid profile. Patients with non-obstructive azoospermia, associated with meiosis arrest, may have unique lipidomic characteristics of seminal plasma, which in the future will make it possible to differentiate various variants of severe male infertility using non-invasive methods.